Pengaruh Electronic Word Of Mouth dan Brand Trust Terhadap Keputusan Pembelian Tiket Pesawat Melalui Layanan Tiket.Com - AN, Charles; Alvia A, Indira (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2022)
Along with the rapid development of internet technology, various online travel agents (OTA) were born, one of which is Tiket.com. Even though it has been established longer, Tiket.com is still less competitive with OTA competitors, Traveloka. This is marked by more consumers making purchase decisions through Traveloka than Tiket.com. The purpose of this study is to determine the influence  of electronic word of mouth (EWOM)  and brand trust both partially and simultaneously on the decision to purchase airline tickets through Tiket.com services. This research is a causal associative research using a quantitative approach. Data collection was carried out using questionnaires with a sample of 100 people. The data analysis technique used is multiple linear regression analysis. The result of this study is that EWOM  and brand trust have a positive and significant influence on purchasing decisions, both partially and simultaneously.